The Effect Of Mulch Type On Eggplant Plants Production (Solanum Melongena L.) (International Forum of Researchers and Lecturers, 2024)
The aim’s of this research was to determine the effect of mulch type on the growth and yield of eggplant plants. This research was carried out from February to May 2018. In Fatuquero village, Railaco sub-District, Ermera Municipality, it is located at an altitude of 800 m above sea level. The design used in this research was a single factor Randomized Block Design, namely Mulch (M) which was repeated 4 times, namely M0 = No Mulch (control), M1 = Rice Straw Mulch, M2 = Black Plastic Mulch and M3 = White Plastic Mulch silver. In general, the effect of mulch type provides very significant differences in all growth parameters and yield parameters. The research results showed that the silver white plastic mulch (M3) gave the highest yield, namely 8.03 kg/plot and the lowest yield was obtained in the treatment without mulch (M0) with a value of 4.83 kg/plot.